Assessment of Physicochemical Properties of Wastewater from Waste Stabilization Pond of a Refinery and Petrochemical Industry, Kaduna State, Nigeria - L. E. O. Ameh; D. A. Machido; M. B. Tijjani; G. J. Sow (Journal of Applied Sciences and Environmental Management, 2023)
The wastewater released by refineries and petrochemical industries frequently contain a range of substances categorized as physical and chemical pollutants. The objective of this study was to assess the physicochemical properties of wastewater from waste stabilization pond of a refinery and petrochemical industry, Kaduna, Nigeria using appropriate standard methods. Results obtained showed that the wastewater had an average pH (8.18), temperature (26.29oC), dissolved oxygen (0.86 mg/L), total dissolved solids (195.33mg/L), electrical conductivity (159.71µs/cm) and chloride (40.08mg/L) which were in compliance with the limit set by the Federal Ministry of Environment, Nigeria. However, chemical oxygen demand (65.85mg/L), biological oxygen demand (32.32 mg/L), oil and grease (231.97mg/L), nitrate (16.95mg/L), turbidity (5.37NTU), phosphate (10.06mg/L) and sulphate (140.36mg/L) where found to exceed the permissible limit. The mean concentrations of arsenic (4.59mg/L), nickel (0.15mg/L), iron (0.62mg/L), lead (0.67mg/L), cadmium (0.04mg/L) and chromium (0.29mg/L) were higher than the acceptable limits. However, cobalt (0.16mg/L), zinc (0.30mg/L), manganese (0.56mg/L), copper (0.13mg/L) and magnesium (1.65mg/L) contents were within the acceptable limits. These results point the need for adequate treatment of wastewater from petrochemical and related industries using appropriate wastewater treatment technologies. Continuous release of this wastewater into the environment poses great threat to both the environment and public health.